Chromatisch konfokale Triangulation - Hochgeschwindigkeits 3D-Sensorik auf Basis der Wellenlängenschätzung mit optimierten Filtern - Taphanel, Miro (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2018)
A chromatic confocal 3D sensor is proposed. In contrast to the state of the art, which typically uses spectrometers to measure the wavelength, only a few camera channels are used. Each channel has an unique spectral sensitivity ant the optimization of the sensitivity is the main part of the book. Interference filters are optimized for the technical realization.